Optimization of trajectory tracking control of 3-DOF translational robot use PSO method based on inverse dynamics control for surgery application - Ngoc Pham Van Bach (JVE International, 2021)
This research presents an optimal trajectory tracking control method for improving the accuracy of 3-DOF translational parallel robots in the surgery field based on the Particle Swarm Optimization (PSO) method. The 3-DOF translational robot has three translational degrees of freedom, which consists of three arms with three revolute joints and twelve spherical joints. Firstly, the kinematics model is established; and the dynamics equation of the Robot is built by applying the Lagrange equation of the first type, and then the dynamics controller of 3-DOF translational robot is designed base on the dynamics equations. Secondly, a trajectory tracking controller model using the Particle Swarm Optimization based on inverse dynamics controlled method for 3-DOF translational Robot is designed. The control performance results of the proposed controller is evaluated by simulation and compared with the other published research results. Finally, the proposed controller can achieve better tracking performance in comparison with other controllers as Proportional Integral Derivative (PID) controller, GPI controller, and adaptive controller.